(untitled) (ENTHYMEMA, 2022)
The essay examines some contributions published by the poet Durs Grünbein on the occasion of the seventh centenary of Dante’s death. Particular attention is paid to the tercet of Paradiso XXXIII, 94-96, whose meaning and translation engage the German poet since at least 2009. On the basis of the terminology used by Grünbein to describe his transpositions of Dante’s verses in terms of rendering, the essay investigates the influence of Dante in the author’s poetics in the light of the global-digital era starting from the contributions of 2021 and going back to the sources of poetic inspiration, where Grünbein rereads Dante with Descartes and Mandelstam.